Answers

The Brainliest Answer!
2016-03-19T23:39:06+05:30
Total mean =mean of first 13 observation+ mean of last 13 observation - (13th element)

this is because 13 element is taken twice when adding first and last 13 elements

that is
36=32+40-x
x=36
x=36
2 3 2
Please consider making this as the brainiest answer
2016-03-19T23:49:59+05:30
As 25th observation is 36.
the mean of first 13 observation is 32.
the last 13 observation is 40
then, 

13 element is taken twice when adding first and last 13 elements

that is
36=32+40-x
x=36
x=36
1 5 1
Please mark it brainiest answer....................................